Preformulasi, Evaluasi Mutu, dan Inovasi Teknologi Sediaan Padat Berbasis Bahan Alam: Artikel Review - Lexa Putri Amanda; Elsa Novelia; Asty Yolandari; Cindy Pakpahan; Putri Nafisha; Yuhelsa Marsanda; Azmi Habibah; Mutia Mawaddah; Nabilla Aulia Putri; Aufa Nur Asyifa; Muhammad Arif (Jurnal Ilmu Psikologi dan Kesehatan | E-ISSN : 3063-1467, 2026)
Natural medicines are often formulated into solid dosage forms, but the physicochemical properties of herbal extracts, such as hygroscopicity, viscosity, and poor flow characteristics, pose major challenges. This review aims to analyze the progress of pharmacotechnical innovations in pre-formulation, production methods, physical quality evaluation, and release kinetics of herbal solid dosage forms. The method applied is a systematic literature review of 25 research articles from the period 2017-2026 derived from the Google Scholar, PubMed, and ScienceDirect databases. The results of the study indicate that innovations in adsorbent excipients have proven successful in addressing the issue of the stability of thick extract print masses. Recent innovations include technology that converts liquids to solids, improvements in the mechanical structure of plant-based polymer capsules using calcium carbonate, engineering heat-resistant granular matrices, and the use of nanotechnology and inclusion complexes. These innovations have been proven to significantly reduce excessive bitterness and increase the bioavailability of active substances in the body. In conclusion, the combination of rigorous compendial evaluation and smart drug delivery system technology can produce stable, precise, and highly efficacious herbal preparations comparable to modern synthetic drugs.